1990
DOI: 10.1128/aac.34.12.2342
|View full text |Cite
|
Sign up to set email alerts
|

Human safety and pharmacokinetics of a single intramuscular dose of a novel spectinomycin analog, trospectomycin (U-63,366F)

Abstract: In this study, local and systemic tolerance and pharmacokinetics of trospectomycin sulfate in human beings were evaluated for the first time. Trospectomycin sulfate (U-63,366F; trospectomycin) or sterile saline was administered to 96 healthy male volunteers in doses ranging from 0.25 ml (75 mg) to 3.3 ml (1,000 mg) in a single intramuscular iujection in a double-blind, randomized design. Volunteers were screened to establish baseline vital signs and laboratory test values. Pain and tenderness at the injection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The calculated t 1/2 β (1.65 h) obtained in the present study was similar to those reported in cattle (1.0 h) (Caputo, 1995), sheep (1.10 h) (Craigmill et al. , 1995) and humans (1.85 h) (Novak et al. , 1990) and lower than those reported in chickens (3.27 h) (el‐Sayed et al.…”
Section: Discussionsupporting
confidence: 90%
“…The calculated t 1/2 β (1.65 h) obtained in the present study was similar to those reported in cattle (1.0 h) (Caputo, 1995), sheep (1.10 h) (Craigmill et al. , 1995) and humans (1.85 h) (Novak et al. , 1990) and lower than those reported in chickens (3.27 h) (el‐Sayed et al.…”
Section: Discussionsupporting
confidence: 90%